Substitutive Authority Of Minority Shareholders In The Dissolution Of A Limited Liability Company In The Event Of A Vacuum Of Power Within The Board Of Directors - Hilda Bintang Theresia; Sudaryat Sudaryat; Rai Mantili (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
In the practice of limited liability companies, situations often arise where the Board of Directors no longer performs its management functions, causing the company’s decision-making mechanisms to reach an impasse. This situation places minority shareholders in a vulnerable position, even though Law No. 40 of 2007 on Limited Liability Companies (UUPT) has, in principle, provided them with protections and scope of authority. This study aims to analyze the legal authority of minority shareholders in filing a request to convene an Extraordinary General Meeting of Shareholders (EGMS) with the agenda of dissolving the company, as well as to examine the mechanisms for the dissolution and liquidation of the company when the Board of Directors no longer fulfills its obligations. The method used is a normative legal approach through an examination of legislation, legal doctrine, and court decisions, specifically the Mataram District Court Decision No. 21/Pdt.P/2022/PN Mtr as a case study. The research findings indicate that minority shareholders possess legal authority—both substitutive and procedural—to initiate the convening of an Extraordinary General Meeting of Shareholders (EGMS) through a court order as a means of restoring decision-making mechanisms that have stalled due to the Board of Directors’ negligence. The subsequent liquidation mechanism further confirms that executive authority is fully transferred to the liquidator upon appointment, so that the role of minority shareholders is limited to a supervisory function to ensure the accountability of the liquidation process without taking over management functions.